Revenue Losses: Exploring Strategies Required by Managers to Inhibit Movie Piracy - Shaibu Akaeze, Nana Aishat (2016)
The piracy of movie products resulted in 72,000 lost jobs and $4.5 billion in lost wages to the United States economy in 2012. The purpose of this multiple case study was to explore what strategies movie corporation managers use to inhibit piracy of movie products to achieve profitability. The sample consisted of 6 movie industry managers who managed movie corporations for not less than 5 years in New York City. The conceptual framework for this study was based on the general systems theory. Data were collected through face-to-face semistructured interviews. Transcript review and member checking were used to ensure credibility and trustworthiness of the interpretation of participants' responses. The 3 major themes that emerged in the study include the perceived effects of movie industry managers' marketing management strategies, legal management strategies, and customer management strategies for inhibiting product piracy. Findings from this study contribute to social change by indicating strategies that other movie industry managers may use to prevent piracy of product, sustain business, and reduce the negative effects of job loss. The results of this study thus may contribute to the prosperity of movie industry leaders, employees, their families, communities, and the local economy